Based on PERCLOS - Driver Fatigue Detection System - Xu, Haoyang (Journal of Theory and Practice of Management Science, 2025)
This article describes the mechanism of PERCLOS testing for driving fatigue and introduces fatigue algorithm recognition. Firstly, use a skin color model to roughly detect the entrance and exit areas of the face, and accurately locate the eyes based on the geometric features of the driver's face. Then, based on the number of white pixels in the eye area and the duration of eye closure, determine the driver's condition. Finally, the fatigue detection decision was implemented, and the results showed that the system could accurately locate the eyes and determine the driver's fatigue status.